2018
DOI: 10.1016/j.comtox.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

BCScreen: A gene panel to test for breast carcinogenesis in chemical safety screening

Abstract: A B S T R A C TTargeted gene lists have been used in clinical settings to specify breast tumor type, and to predict breast cancer prognosis and response to treatment. Separately, panels have been curated to predict systemic toxicity and xenoestrogen activity as a part of chemical screening strategies. However, currently available panels do not specifically target biological processes relevant to breast development and carcinogenesis. We have developed a gene panel called the Breast Carcinogen Screen (BCScreen)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 56 publications
(95 reference statements)
0
22
0
Order By: Relevance
“…Fingerprints including biomarkers related to DNA, epigenetic, proteins and adducts can describe more directly mechanisms of carcinogenicity initiated by the exposure to environmental chemicals, thereby strengthening biological plausibility. They can also be applied to traditional epidemiological studies and be used as trackers to identify specific type of cancers (Ceccaroli et al 2015 ; Grashow et al 2018 ; Madia et al 2019 ). In our hypothesis, we consider that three main toxicity endpoints such as toxicokinetics, skin sensitisation and genotoxicity may be supplemented with the inclusion of information for ED mode of action, ToxCast, EpigeneticTox, and human information for biomarkers and SNPs and susceptibility factors for cancer disease (Fig.…”
Section: New Paradigms For Sustainable Safety Testingmentioning
confidence: 99%
“…Fingerprints including biomarkers related to DNA, epigenetic, proteins and adducts can describe more directly mechanisms of carcinogenicity initiated by the exposure to environmental chemicals, thereby strengthening biological plausibility. They can also be applied to traditional epidemiological studies and be used as trackers to identify specific type of cancers (Ceccaroli et al 2015 ; Grashow et al 2018 ; Madia et al 2019 ). In our hypothesis, we consider that three main toxicity endpoints such as toxicokinetics, skin sensitisation and genotoxicity may be supplemented with the inclusion of information for ED mode of action, ToxCast, EpigeneticTox, and human information for biomarkers and SNPs and susceptibility factors for cancer disease (Fig.…”
Section: New Paradigms For Sustainable Safety Testingmentioning
confidence: 99%
“…Furthermore, biomarker gene signatures currently in use for early cancer diagnosis and clinical treatment decisions can be exploited to prioritise chemicals in need of thorough assessment for a specific cancer type. Grashow and co-workers (Grashow et al, 2018) have recently proposed an example of this type of approach. The authors have identified several occupational and environmental chemical classes that increase breast cancer risk.…”
Section: Recommendations For Adapting Carcinogenicity Assessment To Mmentioning
confidence: 99%
“…However, thousands of chemicals remain untested for their breast carcinogenic potential. Therefore, the authors have used biomarker gene kits from clinics to prioritise and curate a panel of genes which can serve as a biomarker of mammary toxicity and breast carcinogenesis (Grashow et al, 2018; Rodgers et al, 2018).…”
Section: Recommendations For Adapting Carcinogenicity Assessment To Mmentioning
confidence: 99%
See 2 more Smart Citations